Speech Recognition : Study of Fundamental Frequency as a Variable - Ashok Kumar (Journal of All India Institute of Speech and Hearing, 1970)
The computer has invaded all walks of life of human beings. Speech Pathology is no exception to this. The computer has been used extensively for Speech analysisand synthesis for the diagnosis and treatment of speech disorders. However, speech recognition has not been used well for the purpose of speech andlanguage therapy, even though it has lot of potentials in terms of providing reinforcement to the cases, motivation and drill to the cases. Presently someof the attempts have been made to use this for articulation testing and therapy. In this context, it was necessary to review the literature regarding speechrecognition and also study possible variables affecting speech recognition. Therefore, this is part of a proposed extensive study on application of speechrecognition in speech therapy and diagnosis.